2019
DOI: 10.1016/j.cogdev.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Verbal framing and statistical patterns influence children’s attributions to situational, but not personal, causes for behavior

Abstract: Adults from Western cultures attribute others' behavior to personal causes more readily than situational causes; however, little research has explored the developmental origins of this attributional bias. Research has shown that children can use both the statistical patterns present in observed behavior, as well as the verbal framing of the behaviors, to infer personal causes.However, research has not explored whether children also use these factors to infer situational causes. The present study examined the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
(92 reference statements)
3
8
0
Order By: Relevance
“…In particular, Peretz-Lange and Muentener (under review) found that extrinsic framing reduced young children's personal attributions relative to both intrinsic and neutral framing, which yielded similar rates of attributions. We replicated this asymmetric impact of framing among young children, supporting the idea that young children hold a default bias toward personal attributions that can be disrupted by extrinsic framing, but not enhanced by intrinsic framing (see also, Peretz-Lange & Muentener, 2019).…”
Section: Relations Between Verbal Framing Attributions and Social Preferencessupporting
confidence: 70%
See 1 more Smart Citation
“…In particular, Peretz-Lange and Muentener (under review) found that extrinsic framing reduced young children's personal attributions relative to both intrinsic and neutral framing, which yielded similar rates of attributions. We replicated this asymmetric impact of framing among young children, supporting the idea that young children hold a default bias toward personal attributions that can be disrupted by extrinsic framing, but not enhanced by intrinsic framing (see also, Peretz-Lange & Muentener, 2019).…”
Section: Relations Between Verbal Framing Attributions and Social Preferencessupporting
confidence: 70%
“…Research on children's causal reasoning has used a variety of methods to assess children's attributions, including children's free-response explanations ("Why did Josie play on the diving board?" Peretz-Lange & Muentener, 2019;Seiver, Gopnik, & Goodman, 2013; "Why did Sally get hungry? " Harris, German, & Mills, 1996; "Why is this block staying straight?…”
Section: Relations Between Explanations and Interventions For Status Disparitiesmentioning
confidence: 99%
“…In other words, structural attributions might enable children to causally account for observed disparities while avoiding personal attributions and their pernicious consequences. Optimistically, emerging research supports the idea that even young children are capable of forming structural attributions (Hussak and Cimpian, 2015;Vasilyeva et al, 2018;Peretz-Lange and Muentener, 2019;Yang et al, 2021). The present study contributes to this emerging research area in a few ways: First, the research on structural attributions often involves explicitly telling children about the cause of a given disparity (e.g., Hussak and Cimpian, 2015;Sutherland and Cimpian, 2019;Rizzo et al, 2020;Dunlea and Heiphetz, 2021).…”
Section: Personal Attributions and Prejudice Developmentsupporting
confidence: 55%
“…We are motivated by the research showing that children form and revise their causal knowledge in social collaboration with parents and caregivers (see Legare et al, 2017 for a review), and that children can learn and generalize new types of explanations when provided with examples of them from an adult (Walker et al, 2015;Lombrozo et al, 2018). In particular, we draw from research demonstrating that verbally highlighting extrinsic causes can disrupt children's default tendency to form personal attributions (Vasilyeva et al, 2018;Peretz-Lange and Muentener, 2019). For example, Peretz-Lange and Muentener (2019) verbally framed characters' behaviors in either intrinsic, extrinsic, or neutral terms, and then assessed preschoolers' attributions for the behaviors.…”
Section: Personal Attributions and Prejudice Developmentmentioning
confidence: 99%
See 1 more Smart Citation